An analysis of renewable energy technologies using two simulation software: homer and RETScreen - Ramli, Mohd Sufian; Abd Wahid, Siti Sufiah; Hassan, Khairul Kamarudin (UiTM Johor, Segamat, 2017)
This paper concerns on modelling renewable energy technologies including PV standalone system (PVSS) and wind standalone system (WSS) as well as PV-wind hybrid system (PVWHS). To evaluate the performance of all power system configurations in term of economic analysis and optimization, simulation tools called HOMER and RETScreen are used in this paper. HOMER energy modeling software is a powerful tool for designing and analyzing hybrid power systems, which contains a mix of conventional generators, wind turbines, solar photovoltaic’s, hydropower, batteries, and other inputs. RETScreen uses a Microsoft Excel-based spreadsheet model that consists of a set of workbooks which calculates the annual average energy flows with adjustment factors to account for temporal effects such as solar-load coincidence. Sizes of equipments are calculated and inserted as inputs to HOMER and RETScreen. The result obtained are analyzed and discussed. The cost per kWh to generate electricity using the standalone system to supply the average demand of 8.4kWh/day ranges between RM 1.953/kWh to RM 3.872/kWh. It has been found that the PVSS gives the lowest cost of energy compared to the other proposed two technologies that have been simulated by using HOMER and RETScreen.